The Development of the Faculty of Economics: Issues and New Opportunmes - Galinienė, Birutė (Ekonomika, 2005)
The purpose of the article is to describe and assess the role and the place of the Faculty of Economics of the Vilnius University in Lithuanian science and economic system by taking into consideration existing research, academic and technical resources, and to disclose existing objective and subjective constraints for the development of research and studies at the faculty. An appropriate attention is paid to discover possibilities for the improvement of the content and quality of study programmes. A particular attention is paid to the quality and effectiveness of doctor studies which remains an acute issue for the faculty. Not less important is the issue of international cooperation. The author seeks to reveal where the Faculty of Economics is at present in the process of internationalization.The article states that the Faculty of Economics is one of the most popular and largest faculty in number of students and selection of study programmes not only at Vilnius university but also among corresponding faculties of other Lithuanian universities. Such a statement is based on the high competition among applicants and good programme ratings.During last five years significant changes took place in the organizational and management structures, and facilities of the faculty. Having a permanent shortage in public funding the faculty each year allocates more and more of its earned revenues for the refurbishment of auditorium and rooms, for the equipment of students’ and teachers’ working places with computer and other modern equipment and their constant upgrading, for the purchase of literature, for promotion of personnel at the faculty.Financial resources of the faculty and university and existing in Lithuania legislation are not favourable to retain and rejuvenate scientific and academic staff and stimulate their professional growth. Public financing model enforced in the Law of Higher Education in fact encourages the achievement of quantitative indicators but not study quality.The improvement of study programmes and their implementation is to large extent related to rejuvenation of academic staff, strengthening of research, increase of academic staff motivation to improve their qualification and work standards, implementation of modern study methods, formation of students’ practical skills.Setting of research priorities, its effectiveness is very related to the system of assessment of research results and the incentives for their enhancement. In assessing institutions of higher education among other indicators such as international recognition, academic potential, facilities, international relations are research results indicating a possibility of university to support studies with relevant research outputs. Unfortunately, existing research outputs’ assessment system is based on quantitative indicators and takes into consideration mainly publications in international journals but ignores the impact of publications on national economic development. In order to enhance research activities the faculty three years ago established research incentives system. The system is being developed each year.Doctor studies are important means for the development of chairs and the faculty, and is a precondition to ensure a unity between research and studies. Unfortunately, the effectiveness of doctor studies at the faculty is low. Such study level is a result of both objective and subjective reasons and problems such as the selection of good doctor students and their supervisors, organization of doctor studies etc.The academic staff and students of the faculty are active in joint international projects and programmes, in students’ and teachers’ exchanges. Number of ERASMUS agreements during last five years doubled and number of exchange students increased considerably. The faculty is leading faculty at the university in number of courses taught in foreign languages and has developed a full master programme in English language.